Event Management Analysis of the Java International Vape Expo 2024 in Creating a Connecting Space for Indonesian Vapers - Salsadilla, Gadisha; Frisiska, Frisiska; Heykal, Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Humans are cultural creatures. Each region, tribe, language and group can have a different culture. Culture is influenced by the surrounding environment. Habits that are continuously carried out together will become a popular culture that is easily spread like vaping. Vaping is an innovation in technology and is a transformation from conventional cigarettes to electronic cigarettes. Throughout its journey, vaping has experienced many changes, starting from regulations, form, type, to function. Some people use vape because of necessity, and some people use vape because of their lifestyle. This lifestyle is based on the word "hobby" and when individuals meet other individuals with the same background there will be something in common. From this new communities emerged with the same object. The growth of the community will provide opportunities for many producers, especially in the vape sector. Producers use events as a commercial medium. One of the biggest vape events in Indonesia is the Java International Vape Expo 2024. This research will analyze event management and its correlation with the vapers community in Indonesia using qualitative methods. Java international vape expo 2024 not only showcases vape products and innovations, but is also a platform to improve the vape community through social interaction and learning. Every step from initial research to final evaluation plays an important role in creating an unforgettable experience for all involved, especially in realizing the "Indonesian Vapers People's Party". So this event is able to create a space for connection between vapers throughout Indonesia.